Analysis of Sharia Hospital Services: Systematic Literature Review - Aulia, Mirza; Srimayarti, Berly Nisa; Aini, Rafika; Yudhanto, Satrio Bhagas; Hariani, Meta (Universitas Muhammadiyah Yogyakarta, 2025)
Indonesia, the country with the largest Muslim population and a strong Islamic influence, is a democratic nation where there is a demand for Sharia-compliant healthcare services. Hospitals adhering to these principles are known as Sharia hospitals. This study aims to analyze healthcare services provided by Sharia hospitals. This research employed a Systematic Review method using the PRISMA approach, collecting 301 articles from four major databases: PubMed, Google Scholar, ScienceDirect, and Springer Link. After screening, 51 duplicate articles were removed, and 204 articles were eliminated for not meeting the selection criteria. At the eligibility stage, 40 articles were deemed irrelevant, leaving six articles for analysis. In Indonesia, Sharia hospitals operate according to DSN-MUI Fatwa No. 107/DSN-MUI/X/2016, which outlines operational guidelines, including service provisions, the use of halal products, and Sharia-compliant financial management. Healthcare services must align with both medical and Sharia standards, emphasizing humanity, transparency, and fairness. Hospitals must provide not only medical care but also spiritual consultations and guidance for worship. Medications and products must be halal-certified, except in emergencies where informed consent is required. Financial management must comply with Sharia principles, avoiding riba (usury). Compared to Malaysia, where Sharia principles are also emphasized, Indonesia has stricter regulations and standards for Sharia implementation in hospitals. Sharia hospitals in Indonesia integrate Sharia principles comprehensively, ensuring fair and transparent medical services, the use of certified halal products, and Sharia-compliant financial management, which is in line with DSN-MUI Fatwas and patient spiritual needs.